Kualitas Empati dalam Komunikasi Digital sebagai Cermin Kesejahteraan Subjektif Emerging Adults Pengguna Media Sosial di Banyumas - Andika Agus Setiawan; Nisa Arfiana Nurbaeti; Nimas Wukir Wulandari; Gisella Arnis Grafiyana (Jurnal Ilmiah Penelitian Psikologi, 2026)
Digital communication has become a primary mode of social interaction among emerging adults, raising important questions about its psychological impact. This study examined the influence of digital empathy on subjective well-being among emerging adults who actively use digital media. Digital empathy was measured using the Digital Communication Empathy Scale (DCES) (α = 0.966), which encompasses six dimensions: digital emotion match, digital perceived empathic accuracy, digital perspective-taking, digital sympathy, digital personal distress, and digital empathic anger. Subjective well-being was measured using the BBC Subjective Well-Being Scale (BBC-SWB) (α = 0.951), covering psychological well-being, physical health and well-being, and relationships. This study employed a quantitative regression design involving a sample of 118 emerging adults’ males aged 18-29 and females aged 18-27 in Banyumas who regularly use digital communication, selected through purposive sampling. Results indicated that digital empathy significantly and positively predicted subjective well-being (F (1,116) = 294.447, p < .001, R² = .717), which indicates that DCE accounts for 71.7% of the variance in SWB, meaning that individuals’ well-being can be inferred from their empathetic communication on digital media.